Eksistensi Awig-Awig Desa Adat Legian dalam Melestarikan Pariwisata Budaya pada Era Globalisasi (Studi Kasus di Desa Adat Legian, Kecamatan Kuta, Kabupaten Badung) - I Wayan Agus Rama; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2022)
Legian Traditional Village has experienced the influence of the globalization process. Awig-Awig is a traditional village which is used to regulate the welfare of indigenous peoples and the sustainability of traditional villages in maintaining traditions and culture in the midst of tourism development. The formulation of the problem: 1) What is the position and function of the Awig-Awig in Legian Traditional Village in preserving cultural tourism in the era of globalization? 2) What are the efforts to filter the negative impacts of globalization in preserving cultural tourism in the Legian Traditional Village?. This study uses empirical legal research methods. The results of the study indicate that the position and function of the Awig-Awig in Legian Traditional Village is able to coexist with the globalization paradigm. The globalization process accompanied by the strengthening of Awig-Awig which is implemented based on Palet 5 Indik Drewen Pawos Village 26, as a reference for preserving cultural tourism in the Legian Traditional Village. Efforts to filter the negative impacts that occur, it is necessary to maintain the socio-cultural aspect by filtering the incoming culture and strengthening the preservation of culture with local wisdom referring to the Awig-Awig contained in Palet 5 Indik Drewen, Pawos Village 26.